The use of Nicotinamide in Parkinson’s disease; A Possible path to the future. Review Article - Sarah F Fahmy; Mona Alshahawy; Nourhan Mohamed; Nora Gamal; Samar Abdelazim; Nadia Abdelsalam; Hend Abdelrahim; Reem H Shehab; Lamia El Wakeel (Archives of Pharmaceutical Sciences Ain Shams University)
Increasing the prevalence of Parkinson’s disease is an alarming sign that needs attention, so focusing on new medications and regimens which play an important role in prevention and treatment becomes a point of concern. Parkinson's disease is the second neurodegenerative disorder caused by the interplay between different mechanisms that are related to genetics, environment, and other factors. One of the potential treatment options under research is nicotinamide which may act as a neuroprotective agent. Although nicotinamide is accepted as a therapeutic agent in many diseases, its action as a Nicotinamide adenine dinucleotide (NAD) precursor against oxidative stress needs to be proved in Parkinson’s disease. Here, based on the current literature, we provide a thorough overview of nicotinamide usage in medicine. We summarize chemistry, uses, side effects, different mechanisms, and all available preclinical and clinical data about the activity of nicotinamide. Nicotinamide increases cytoprotection, the release of dopamine, and decreases oxidative stress of mitochondria. As a consequence, we believe that nicotinamide may become a potential drug in the treatment of Parkinson’s patients.